Lipid X ameliorates pulmonary hypertension and protects sheep from death due to endotoxin. - Golenbock, D T (1987)
Lipid X (2,3-diacylglucosamine-1-phosphate) is a novel monosaccharide precursor of lipid A that has some of the physiologic activities of endotoxin but little toxicity. To determine whether lipid X would interfere with the toxic effects of endotoxin, we pretreated sheep with either 100 or 200 micrograms of lipid X per kg of body weight and then challenged them with a potentially fatal dose of Escherichia coli endotoxin (20 micrograms/kg). Twenty-one sheep underwent pulmonary artery catheterization and were monitored for changes in pulmonary artery pressure, temperature, pH, partial O2 pressure, partial CO2 pressure, blood pressure, and cell counts over 7 h. Overall mortality for control animals was 37% versus 5.3% for pretreated animals. None of the 13 animals pretreated with 100 micrograms of lipid X per kg died. These differences in survival were significant (P less than 0.05). Animals pretreated with 100 micrograms of lipid X per kg had significantly lower pulmonary artery pressure during both phases 1 and 2 of endotoxin-induced pulmonary artery hypertension. A higher dose of lipid X, 200 micrograms/kg, produced pulmonary hypertension. Perhaps because lipid X is a subunit of lipid A, lipid X shows a partial pyrogenic effect while also decreasing the pyrogenic activity of complete lipopolysaccharide (LPS). Lipid X did not prevent endotoxin-induced neutropenia or moderate hypotension in response to LPS. Lipid X is a potential prototype compound for a new type of chemotherapy directed at blocking the harmful effects of LPS during bacterial septicemia.